Changing roles of the government and markets in Tanzania : implementation, impacts and problems of a liberalized agricultural marketing system : proceedings of the 3rd Scientific Conference of the Agricultural Economics Society of Tanzania (AGREST) held at SADC Forestry Training Centre, Arusha 4-6 August 1999 (AGREST conference series, 2000)
Most of the contributed papers addressed the issues of marketing of agricultural products and reform policies. One paper was on the role of government and markets in food security. Two papers were on maize marketing and another two papers addressed issues of traditional cash crop marketing. Improved seed marketing, dairy marketing, capital markets, structural adjustment and deforestation had one paper each